The Influence of Service Quality and Facility Completeness on Outpatient Satisfaction at Syekh Yusuf Regional Public Hospital, Gowa Regency (International Forum of Researchers and Lecturers, 2025)
Background: Patient satisfaction is widely recognized as a key indicator of hospital service quality. At Syekh Yusuf Regional Public Hospital, the 2024 Patient Satisfaction Index (PSI) recorded scores of 85.79 in the first semester and 84.07 in the second semester—both below the national benchmark of ≥90%. These results highlight the need for a deeper assessment of factors shaping patient satisfaction, especially the roles of service quality and facility completeness. Objective: This study aimed to examine how service quality and the completeness of hospital facilities influence the satisfaction of outpatients at Syekh Yusuf Regional Public Hospital, Gowa Regency. Methods: The research employed a quantitative approach with a cross-sectional design. Using accidental sampling, data were obtained from 204 respondents. A structured, validated, and reliable questionnaire was used to gather responses. Statistical analyses included Chi-Square tests and multiple linear regression, performed with SPSS version 25. Results: Analysis revealed that service quality did not have a statistically significant impact on satisfaction (p = 0.047 > 0.05). Conversely, facility completeness had a significant positive effect (p = 0.004 < 0.05). When analyzed simultaneously, both variables accounted for 60.8% of the variation in patient satisfaction. Key facility aspects influencing satisfaction included the availability of comfortable waiting areas, clean and functional toilets, and well-maintained physical amenities. Barriers such as delayed doctor arrival and extended waiting times were reported to reduce satisfaction levels. Conclusion: The completeness of hospital facilities was found to be a stronger determinant of outpatient satisfaction compared to service quality. To foster sustained satisfaction, hospital management should focus on upgrading infrastructure, ensuring adequate seating, maintaining hygiene, improving air conditioning, and optimizing queuing systems.